MOTIVASI SISWA DALAM MEMILIH LINTAS MINAT BIOLOGI DI SMAN PEKANBARU TAHUN PELAJARAN 2018/2019 - Pratiwi, Devi Octavia; Natalina L, Mariani; Fauziah, Yuslim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aimed to know the motivation of the students in the lesson 2018/2019 Year Soweto SMAN in selecting the cross-section of interest in biology. This research was carried out in SMA Negeri Soweto in October – November 2018. The population in this research is the whole grade X IS SMAN 1 Soweto, Soweto, and 14 SMAN SMAN 10 Soweto school year 2018/2019 totalling 186 people. This research is descriptive research. Techniques in determination of sample is Purposive sampling. Measured parameters are indicators of motivation that is interest, tenacious, persevering, a sense of happy and confident. Based on the research results obtained the motivation of students against the indicators of interest obtained average 64% with the category Being, motivation of students against the tenacious indicators obtained average 59% with categories Being, motivation of students against the indicators of persevering obtained 60% with the average category are, motivation of students against the indicators of pleasure obtained average 61% by category, and the motivation of students against the indicators of confidence gained average 60% by category. From the results it can be concluded that the motivations of students against the cross-interest biology 61% average obtained by category.Key Words: Motivation, interest in biology, Social(IS)